The Artistic Merits of Mirza Khan Ansari’s Ghazal - Rahman, Bacha; Marjan, Asal (Makhz (Research Journal), 2025)
This Article explores the artistic merits of Mirza Khan,s Ghazals,a wel khnown poet of the Roshnite school of thought.As a pioneer of romanticism in pashto literature,Mirza Khan,s poetry masterfully intertwines religious, Sufi, philosophical and romantic themes, showcasing his artistic genius. His ghazals exemplify the artistic beauties of Pashto poetry, featuring a rich tapestry of figurative language. metaphors, and symbolism. This study highlights Mirza Khan,s innovative use of language, imagery, and emotional depth, demonstrating how his ghazals emboddy the essence of artistic merits. This article sheds light on Mirza Khan,s enduring impact on pashto literature and his continued relevance in contemporary literary discourse.